Learning and new voices: Lesbian development and the implications for adult education - Diane Resides (Adult Education Research Conference, 1996)
This study contributes to the understanding of lesbians, an oppressed group of people, from their perspective. Incorporating the unique life experiences of lesbians adds value to the research base of the field. This type of research is necessary to give "voice" to diverse groups in theory building and to reveal the "myths" presented in adult education literature.